Molecular identification of endophytic fungi isolated from the tuber of Dahlia variabilis and exploration of their ability in producing ÃŸ-galactosidase - SARYONO SARYONO; SENJAVI RAKHMANA; FITRI RAHAYU; AULIA ARDHI; RUSLI RUSLI; NOVA WAHYU PRATIWI; TITANIA T. NUGROHO (Society for Indonesian Biodiversity, 2017)
Abstract. Saryono, Rakhmana S, Rahayu F, Ardhi A, Rusli, Pratiwi NW, Nugroho TT. 2017. Molecular identification of endophytic fungi isolated from the tuber of Dahlia variabilis and exploration of their ability in producing ÃŸ-galactosidase. Biodiversitas 18: 145-152.LBKURCC67 and LBKURCC69 were endophytic fungi isolated from the tubers of dahlia (Dahlia variabilis) in Padang Panjang, West Sumatra. This study aimed to identify the microscopic and molecular characteristics of endophytic fungi LBKURCC67 and LBKURCC69 based on ITS-rDNA region sequences and determine the ability of the isolates to produce Î²-galactosidase. Microscopic characteristic of LBKURCC67 and LBKURCC69 indicated that both isolates belonged to Fusarium sp. Furthermore, DNA sequence analysis based on mega BLAST program showed that LBKURCC67 was identified to be Fusarium solani with 99% homology and LBKURCC69 showed the perfect homology similarity with Fusarium oxysporum. Meanwhile, Î²-galactosidase activity was determined based on the amount of o-nitrophenol produced from the substrate o-nitrophenil-Î²-D-galactopiranoside, whilst the specific activity was indicated by activity per unit of proteins. The result showed that both fungi could produce Î²-galactosidase. However, the enzyme activity did not increase significantly at various production times of 2, 4, 6, 8, and 10 days. The highest enzyme activity of LBKURCC67 and LBKURCC69 were 0.163 Â± 0.064 U/mL (at day 8) and 0.126 Â± 0.039 U/mL (at day 2) respectively. LBKURCC69 showed higher specific Î²-galactosidase activity (1.886 Â± 0.277 U/mg) than LBKURCC67 (1.179 Â± 0.081 U/mg). Keywords: ÃŸ-galactosidase, dahlia tuber, endophytic fungi, Fusarium, ITS-rDNAÂ